The President of the Republic of Poland as the guardian of the constitution - Rakowska, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Pursuant to Art. 10 and 126 of the Constitution of the Republic of Poland, the President is not only the organ of the executive authority, but also the authority representing the state and the authority executing the so-called arbitration. Assigning the role of the guardian of the constitution to the President falls within his role as an arbiter. The idea of entrusting the president with the function of the organ protecting the constitution was repeated in the drafts of the constitution, which the National Assembly worked on in the years 1994–1997. The provision of the Constitution that the President shall ensure observance of the Constitution means that he is to be the guarantor of constitutional axiology, which may be expressed in the exercise of various powers. Finally, the President – as the guardian of the Constitution – is himself in a special way obliged to comply with its provisions. It is obvious that the President of the Republic of Poland, as the arbiter upholding the values and norms of the Constitution, cannot himself violate the fundamental law.